The Favorable Effect of Empagliflozin on Erectile Function in an Experimental Model of Type 2 Diabetes. Issue 9 (23rd August 2018) - Assaly, Rana; Gorny, Diane; Compagnie, Sandrine; Mayoux, Eric; Bernabe, Jacques; Alexandre, Laurent; Giuliano, François; Behr-Roussel, Delphine
Abstract: Introduction: Following the results of the EMPA-REG Outcome trial, we hypothesized that empagliflozin, a highly potent and specific sodium/glucose cotransporteur 2 inhibitor, could improve type 2 diabetes mellitus (T2DM)-associated erectile dysfunction (ED), a highly prevalent complication of T2DM, very often coexisting with cardiovascular complications and considered as a prognostic factor of cardiovascular disease in men with diabetes. Aim: To investigate the effects of chronic treatment with empagliflozin on ED in a T2DM rat model in the presence or absence of sildenafil. Methods: Male Goto-Kakizaki (GK), a model of T2DM, and age-matched Wistar rats received placebo or empagliflozin treatment at 25.3 ± 0.9 mg/kg/d for 4 weeks. Then, the in vivo effect of empagliflozin on erectile function was assessed by electrical stimulation of the cavernous nerve at different frequencies under anesthesia in the presence or absence of acute intravenous injection of sildenafil. Endothelium-dependent, -independent, and nitrergic relaxations of cavernosal strips from the rats were studied. Main Outcome Measures: Body weight, food consumption, metabolic parameters, plasma inflammation biomarkers, and in vivo erectile responses elicited by electrical stimulation of the cavernous nerve in empagliflozin-treated and untreated GK rats and control Wistar rats were assessed and followed by concentration or frequency response curves to endothelium-dependent, -independent, and nitrergic relaxations of cavernosal strips from these rats. Results: Chronic empagliflozin followed by acute sildenafil significantly improved erectile responses in adult GK rats (n = 12–15/group). Ratios of intracavernous pressure and area under the curve/mean arterial pressure during the electrical stimulation were significantly increased in empagliflozin-treated vs untreated GK rats. Nitrergic relaxations of cavernosal strips from GK rats were significantly increased with empagliflozin compared with placebo. Moreover, the effect of sildenafil on erectile function was not altered by empagliflozin treatment. Clinical Implications: Empagliflozin may benefit T2DM patient with ED. Strengths & Limitations: The mechanism(s) by which empagliflozin shows favorable effect on erectile function in GK rats needs to be further elucidated. Conclusion: Empagliflozin shows favorable effect on erectile function in diabetic GK rats mediated by an improvement of nitrergic relaxation of erectile tissue. Whether this favorable effect on ED in the experimental context of T2DM is due to better glycemic control or to another effect of empagliflozin deserves further investigation.